Metabolism Controls the Balance of Th17/T-Regulatory Cells - Sun, Licheng; Fu, Jinrong; Zhou, Yufeng (Frontiers in Immunology, 2017)
Accumulating evidence indicates that metabolism reprogramming is critically important to T cell differentiation, and manipulating metabolic pathways in T cells can shape their fate and function. During T cell differentiation, metabolism provides T cells with energy as well as precursors for various biological processes. Some key metabolic reactions such as glycolysis, oxidative phosphorylation and fatty acid oxidation (FAO) are also considered to play important roles in T cell activation and differentiation. In this review, we will explain why cellular metabolism is important for the Th17/Treg balance and how metabolism reprogramming impacts this balance. Moreover, we will also discuss some important metabolic sensors, such as mTOR, AMPK and some nuclear receptors. In addition, we will review specific small molecular compounds, which can shift the Th17/Treg balance and, therefore, have promising therapeutic roles. Finally, potential methods of manipulating Th17 cell metabolism for treating Th17-associated diseases will be discussed.